Noise Reduction Technique for Heart Rate Monitoring Devices - Q.H Hii; Reza Firsandaya Malik (ICON-CSE, 2014)
Electrocardiogram (ECG) signal has been widely used to detect the heart rate of the human, and it is useful in cardiac pathology. ECG detects several heart diseases of the patients. Wearable technology comes to be conducted as work as the monitoring devices to get the ECG signal directly from the patients. However, the movement of the patients will cause noises which interfere the result of the ECG. To overcome this problem, the digital filter is proposed to be designed and used in getting an accurate ECG signal. The filtering ECG results give likely in analysing the heart disease.The structures and the coefficients of the digital filters are designed using Filter Design & Analysis (FDA) tool in MATLAB. The analysis of magnitude responseis done in two type of the digital filter - the infinite impulse response (IIR) and finite impulse response (FIR). This paper evaluatesthat the FIR digital filter is more stable and better to be used in removing noise from ECG signals.